Nadia Boulanger : Thoughts on Music - Francis, Kimberly A., 1979-; Francis, Kimberly A., 1979-; Brooks, Jeanice; Brooks, Jeanice (Book collections on Project MUSE., 2020)
"The first collection ever of essays and reviews by the renowned pedagogue, composer, and conductor, providing fresh perspectives on her musical influence and impact"--